Evidence of directed interactions between individuals in captive flamingo flocks - Rose, Paul E.; Croft, Darren P. (Wildfowl, 2015)
Information on social behaviour traits can be inferred from observed associations or measured as the frequency of direct interactions between individuals. For some species,Â information on interactions between individuals, and the form that these interactionsÂ take, is limited. This paper describes three social interactions (affiliative, mate-guardingÂ and directed aggression) seen in captive flamingos (Phoenicoparrus sp. and PhoenicopterusÂ sp.) that could be of help to those studying flamingo social behaviour, by addingÂ explanation of direct interactions to the overall flamingo ethogram. Information onÂ how flamingos organise their social structure appears infrequently in the literature, andÂ what (if any) specific social interactions are performed from one bird to another canÂ be lacking in description and definition. The behaviours explained in this paper provideÂ an insight into the social lives of flamingos that can give support to further, deeper,Â studies into social hierarchy and social affiliation.